Design of flower transplanting mechanisms based on double planet carrier non-circular gear train with complete rotation kinematic pair - Zhao, Xiong; Ma, Xingxiao; Liao, Hongwei; Xiong, Yongsen; Xu, Yadan; Chen, Jianneng (International Journal of Agricultural and Biological Engineering, 2022)
In view of the problems of the existing mechanisms based on 2R open-chain planetary gear train for seedling transplanting, such as the bad tracking flexibility, low positioning accuracy, and high structure design difficulties of the mechanisms based on 3R open-chain planetary gear train for seedling manipulation. In this study, a transplanting mechanism based on the solution domain synthesis of a 3R open-chain-based complete rotation kinematic pair, a gear train with a single cycle integral rotating pair, is designed. The Burmester curve equation is derived from the given transplanting trajectory and four exact poses corresponding to each other on the rotation center. Then, the open-chain road model of the 3R complete rotation kinematic pair is obtained under the constraint governed by the judgment condition of the hinge integral rotating pair. Meanwhile, combined with our developed in-house optimization software, the solution to the optimal parameters for the transplanting mechanism can be optimized according to the target trajectory. Finally, the feasibility of the design method was verified by transplanting testing, where kale seedlings with ages of about 20 d and heights of about 80-120 mm were used. The experimental results showed that the actual motion trajectory of the prototype is basically identical to the theoretical trajectory, validating the feasibility of transplanting mechanism design, parts processing, and test-bed construction. Through the statistical analysis, the average success rate of transplanting is 90.625%, and the reliability of designed mechanism is satisfied. This study provides a promising solution for the seedling transplanting of two-planet scaffold pots. Keywords: 3R open-chain planetary gear train, complete rotation kinematic pair, precise manipulation, plug seedling DOI: 10.25165/j.ijabe.20221503.6957 Citation: Zhao X, Ma X X, Liao H W, Xiong Y S, Xu Y D, Chen J N. Design of flower transplanting mechanisms based on double planet carrier non-circular gear train with complete rotation kinematic pair. Int J Agric & Biol Eng, 2022; 15(3): 9–15.